Harmonized system of quality assessment for electronic components. Fixed capacitors for use in electronic equipment. Blank detail specification. Fixed polystyrene film dielectric metal foil d.c. capacitors. Assessment level E. (15th January 1993) - British Standards Institution,
No abstract available